The ability of Junior High School Science Teacher in Solving The Problems of Torque - Dios Sarkity; Putri Dwi Sundari (Jurnal Geliga Sains: Jurnal Pendidikan Fisika, 2020)
Understanding the concept is an important aspect of solving various physics problems. Understanding the concept will help in understanding the problems, determining problem-solving strategies, and using mathematics appropriately as a problem-solving tool. Lack of conceptual understanding results in the tendency to solve problems by relying solely on formulas without knowing the proper use of formulas according to the underlying concepts of the problem. Various problems related to rotational motion can be explained through the concept of torque. To solve the problem of torque, understanding the concept of torque and mastering the concept of vectors are needed to find solutions to the problems Many of the science teachers have a background in physics education. Science teachers who are a bachelor of physics education should master various physics concepts even though the material is not taught at the junior high school level. Therefore, the authors conducted research to determine the ability of science teachers with an education background in physics education in solving the problems of torque. The study involved 10 science teachers who teach in 10 different schools. This research was a descriptive study with data collection techniques in the form of a questionnaire using an essay question to test the science teacher's ability in solving the problems of torque. The results showed that most of the participants could not solve the problem of torque due to a lack of understanding of the concept in determining the torque generated by forces with various positions.